Temperature, trophic state, and carrying capacity govern pelagic size spectra in the Atlantic Ocean - Ralf Schwamborn; Tim Dudeck; Claire Carré; Gabriel Bittencourt Farias; María Couret; Javier Díaz-Pérez; Mathilde Dugenne; Gabriela Guerra Araújo Abrantes de Figueiredo; Thierry Frédou; Flávia Lucena-Frédou; Xiomara F.G. Díaz; Dawit Yemane; et al. (Progress in Oceanography, 2026)

Assessing local to global associations between mining activity and atmospheric dust - Fakhra Muneeb; Tim Werner; Samira Barzin; Russell Drysdale (Science of The Total Environment, 2026)

Emeishan basalt’s contribution to heavy metals in topsoil (notably cadmium) in Southwest China from soil geochemistry evidence - Fang Yang; Liang Tang; Yang Li; Bo Cheng; Tim T. Werner; Lingfei Qu; Ke Cheng; Aiming Zhang; Junbo Wang; Guikai Li (Acta Geochimica, 2026)

Assessing barriers for energy-efficient retrofits to derive purposive policy recommendations for the residential building sector - Koray Konhäuser; Constantin Rothdach; Nina Schwarz; Tim Werner (Energy Policy, 2026)

Strategic insights into China’s overseas acquisitions: state-owned mineral ventures in Australia - Zhanran Xu; Mark Wang; Tim T. Werner (The Extractive Industries and Society, 2026)

Assessing the impact of metal trade decoupling on energy transition: Evidence from an open-economy DSGE Model - Haoran Duan; Shiwei Yu; Tim T. Werner; Yafang Sun; Jinhua Cheng (Global Environmental Change, 2026)

Evaluating strategic retrofit measures for energy-efficient residential buildings with artificial intelligence - Tim Werner; Koray Konhäuser; Nina Schwarz (Energy and Buildings, 2026)

Sources and transportation of mining metals to soil: A case study from the Lala mining area, Southwest China - Fang Yang; Lei Xu; Liang Tang; Li Dai; Xuemin Liu; Tim T. Werner; Lingfei Qu; Xuefeng Liao; Yang Li; Junbo Wang (Acta Geochimica, 2026)

Lithium in Latin America: A dynamic material flow analysis and mapping CO2, water, and land footprints to 2050 - Estefanía Orquera; Guochang Xu; Tim Werner; Stephen Northey; Oscar Tiku; Damien Giurco; Kazuyo Matsubae (Resources, Conservation and Recycling, 2026)

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Exposure of Australian dams to seismic hazard from proximal faults - Mark Quigley; Tim Werner; Yuxiang Tang; Dan Clark; Jonathan Griffin; Haibin Yang (Environment Systems and Decisions, 2025)
The purpose of this study is to obtain estimates of ground surface rupture and ground motion hazards at standardised scales useful for general reference and regional comparisons of dams (n = 548) registered with the Australian National Committee on Large Dams (ANCOLD). Geospatial and statistical methods are used to investigate the exposure of dams to seismic hazard from 409 faults in the Geoscience Australia Neotectonic Features Database (NFD). We identify 216 faults at distances less than 100 km from 428 dams and measure 4055 fault-to-dam distances. At least 31 dams are located within 1 km of NFD fault traces and at least 16 of these dams could reside within NFD primary fault zones. Estimates of NFD maximum moment magnitudes (M w,max ) from fault area and length regressions range from 5.6 ≤ M w ≤ 7.9. Average (AD) and maximum (MD) NFD fault displacements for M w,max events range from 0.3 m ≤ AD ≤ 4.4 m and 0.9 m ≤ MD ≤ 8.4 m. Distance-probability regressions for distributed ground surface rupture suggest approximately 40 dams have a ≥ 10% probability of ground surface rupture occurring in the area encompassing the dam in a M w,max event. Peak ground accelerations (PGA) and pseudo-spectral acceleration at 1.0 s (PSA[1.0 s]) are estimated for M w,max at dam sites using the same set of ground motion models (GMMs) for the 2023 National Seismic Hazard Assessment (NSHA23), assuming engineering rock site conditions with a time-averaged shear wave velocity between the surface and 30 m sediment depth (VS30) of 760 m/s. Of the 4055 M w,max scenarios considered in total, 3579 M w,max scenarios produce 85th percentile PGA ≥ 0.1 g at dam sites and 2844 scenarios produce 85th percentile PSA[1.0 s] ≥ 0.1 g. Comparison with 1:5,000 annual exceedance probability (AEP) PGA and PSA[1.0 s] estimates from the NSHA23 indicate there are 404 out of 428 dams where NFD M w,max PGA are greater than NSHA23 values, and 422 instances where PSA[1.0] > NSHA23. Proximity to NFD faults imparts a first-order control on relative hazard. A large increase in the number of identified NFD faults over the last decade suggests further research will continue to increase NFD fault populations. NFD fault slip rates and M w,max are important parameters in seismic hazard analysis for many dams but exhibit large epistemic and aleatoric uncertainties. Improving the characterisation of NFD faults through acquisition of direct fault-specific seismic hazard information (e.g., single-event displacements, slip rates, inter-event times, frequency-M w distributions, segmentation scenarios) will assist with hazard profiling for many ANCOLD dams.

Mesoscale cyclonic eddies born in an eastern boundary upwelling system enhance microbial eukaryote diversity in oligotrophic offshore waters - Sven Nicolai Katzenmeier; Maren Nothof; Hans-Werner Breiner; Tim Fischer; Thorsten Stoeck (Deep Sea Research Part II: Topical Studies in Oceanography, 2024)

A comprehensive inventory of Australia's critical minerals: Simplifying the complexity of critical resources - Gavin M. Mudd; Tim T. Werner; Zhehan Weng; Jane Thorne (Resources Policy, 2024)

Island hydrogeology in the tropics: Constraining a 3D variable-density groundwater flow and solute transport model with geophysics - Eddie W. Banks; Saskia Noorduijn; Vincent E.A. Post; Tim Munday; Camilla Sorensen; Kevin Cahill; Phillip Jolly; Joanna Ellis; Adrian D. Werner; Okke Batelaan (Journal of Hydrology, 2024)

Patterns of infringement, risk, and impact driven by coal mining permits in Indonesia - Tim T. Werner; Tessa Toumbourou; Victor Maus; Martin C. Lukas; Laura J. Sonter; Muhamad Muhdar; Rebecca K. Runting; Anthony Bebbington (Ambio, 2024)
Coal mining is known for its contributions to climate change, but its impacts on the environment and human lives near mine sites are less widely recognised. This study integrates remote sensing, GIS, stakeholder interviews and extensive review of provincial data and documents to identify patterns of infringement, risk and impact driven by coal mining expansion across East Kalimantan, Indonesia. Specifically, we map and analyse patterns of mining concessions, land clearing, water cover, human settlement, and safety risks, and link them with mining governance and regulatory infractions related to coal mining permits. We show that excessive, improper permit granting and insufficient monitoring and oversight have led to deforestation, widespread overlaps of concessions with settlements, extensive boundary and regulatory violations, lacking reclamation, and numerous deaths. As the world’s largest thermal coal exporter, Indonesia’s elevated coal infringements, risks, and impacts translate to supply chain, sustainability, and human rights concerns for global coal markets.

Variability of prey preferences and uptake of anthropogenic particles by juvenile white seabream in a coastal lagoon nursery ground - Carolin Müller; Karim Erzini; Tim Dudeck; Joana Cruz; Luana Santos Corona; Felipe Eloy Abrunhosa; Carlos Manuel Lourenço Afonso; Miguel Ângelo Franco Mateus; Cristina Orro; Pedro Monteiro; Werner Ekau (Environmental Biology of Fishes, 2023)
Marine plastic litter, originating from land-based sources, enters the marine environment by passing through coastal ecosystems such as lagoons and estuaries. As early life history stages (ELHS) of many commercially important fish species rely on these transitional areas as nursery grounds, we hypothesized that they encounter a spatial gradient of habitat quality and pollution from inner to outer parts of their vital environment. With sizes < 5 mm, anthropogenic particles (AP), among them microplastic (MP) fibers and fragments, entail a high bioavailability for ELHS of fish, potentially facilitating AP uptake at early developmental stages which may have implications for their survival and growth. This study provides a contextualization baseline between feeding preferences and uptake of AP by the white seabream Diplodus sargus (Linnaeus, 1758) in an estuarine nursery ground on the southern coast of Portugal. Juvenile fish showed a generalized, omnivorous feeding mode with differences in trophic resource utilization between individuals collected at distinct seagrass meadows in the lagoon. A total of 23.13% of the fish ( n = 147) were detected with AP in the gastrointestinal tract, and the mean number of AP per AP-feeding individual was 1.64 ± 1.04, with anthropogenic fibers ( n = 47) occurring more frequently than fragments ( n = 9). Knowledge of the underlying factors for MP ingestion will be greatly enhanced by considering environmental conditions along with species-stage and life-stage specific feeding modes and prey preferences which shape the uptake probability of anthropogenic fibers and fragments.

Rhenium mineral resources: A global assessment - Tim T. Werner; Gavin M. Mudd; Simon M. Jowitt; David Huston (Resources Policy, 2023)

Combination strategy for consistent final, rapid and predicted Earth rotation parameters - Alexander Kehm; Hendrik Hellmers; Mathis Bloßfeld; Robert Dill; Detlef Angermann; Florian Seitz; Urs Hugentobler; Henryk Dobslaw; Maik Thomas; Daniela Thaller; Johannes Böhm; Erik Schönemann; et al. (Journal of Geodesy, 2023)
The accurate knowledge of the Earth’s orientation and rotation in space is essential for a broad variety of scientific and societal applications. Among others, these include global positioning, near-Earth and deep-space navigation, the realisation of precise reference and time systems as well as studies of geodynamics and global change phenomena. In this paper, we present a refined strategy for processing and combining Very Long Baseline Interferometry (VLBI), Satellite Laser Ranging (SLR), Global Navigation Satellite Systems (GNSS), and Doppler Orbitography and Radiopositioning Integrated by Satellite (DORIS) observations at the normal equation level and formulate recommendations for a consistent processing of the space-geodetic input data. Based on the developed strategy, we determine final and rapid Earth rotation parameter (ERP) solutions with low latency that also serve as the basis for a subsequent prediction of ERPs involving effective angular momentum data. Realising final ERPs on an accuracy level comparable to the final ERP benchmark solutions IERS 14C04 and JPL COMB2018, our strategy allows to enhance the consistency between final, rapid and predicted ERPs in terms of RMS differences by up to 50% compared to existing solutions. The findings of the study thus support the ambitious goals of the Global Geodetic Observing System (GGOS) in providing highly accurate and consistent time series of geodetic parameters for science and applications.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Biallelic variants in YRDC cause a developmental disorder with progeroid features - Julia Schmidt; Jonas Goergens; Tatiana Pochechueva; Annika Kotter; Niko Schwenzer; Maren Sitte; Gesa Werner; Janine Altmüller; Holger Thiele; Peter Nürnberg; Jörg Isensee; Yun Li; et al. (Human Genetics, 2021)
The highly conserved YrdC domain-containing protein (YRDC) interacts with the well-described KEOPS complex, regulating specific tRNA modifications to ensure accurate protein synthesis. Previous studies have linked the KEOPS complex to a role in promoting telomere maintenance and controlling genome integrity. Here, we report on a newborn with a severe neonatal progeroid phenotype including generalized loss of subcutaneous fat, microcephaly, growth retardation, wrinkled skin, renal failure, and premature death at the age of 12 days. By trio whole-exome sequencing, we identified a novel homozygous missense mutation, c.662T > C, in YRDC affecting an evolutionary highly conserved amino acid (p.Ile221Thr). Functional characterization of patient-derived dermal fibroblasts revealed that this mutation impairs YRDC function and consequently results in reduced t 6 A modifications of tRNAs. Furthermore, we established and performed a novel and highly sensitive 3-D Q-FISH analysis based on single-telomere detection to investigate the impact of YRDC on telomere maintenance. This analysis revealed significant telomere shortening in YRDC-mutant cells. Moreover, single-cell RNA sequencing analysis of YRDC-mutant fibroblasts revealed significant transcriptome-wide changes in gene expression, specifically enriched for genes associated with processes involved in DNA repair. We next examined the DNA damage response of patient’s dermal fibroblasts and detected an increased susceptibility to genotoxic agents and a global DNA double-strand break repair defect. Thus, our data suggest that YRDC may affect the maintenance of genomic stability. Together, our findings indicate that biallelic variants in YRDC result in a developmental disorder with progeroid features and might be linked to increased genomic instability and telomere shortening.

Backlighting the European Indium Recycling Potentials - Luca Ciacci; Tim T. Werner; Ivano Vassura; Fabrizio Passarini (Journal of Industrial Ecology, 2019)
Summary With increased understanding of the effects of human activities on the environment and added awareness of the increasing societal value of natural resources, researchers have begun to focus on the characterization of elemental cycles. Indium has captured significant attention due to the potential for supply shortages and nonexistent recycling at end of life. Such a combination of potentially critical features is magnified for countries that depend on imports of indium, notably many European countries. With the aims of analyzing the dynamics of material flows and of estimating the magnitude of secondary indium sources available for recycling, the anthropogenic indium cycle in Europe has been investigated by material flow analysis. The results showed that the region is a major consumer of finished goods containing indium, and the cumulative addition of indium in urban mines was estimated at about 500 tonnes of indium. We discuss these results from the perspective of closing the metal cycle in the region. Securing access to critical raw materials is a priority for Europe, but the preference for recycling metal urban mines risks to remain only theoretical for indium unless innovations in waste collection and processing unlock the development of technologies that are economically feasible and environmentally sustainable.

Disturbances of Agency and Ownership in Schizophrenia: An Auditory Verbal Event Related Potentials Study - Tim Bühler; Jochen Kindler; Rahel C. Schneider; Werner Strik; Thomas Dierks; Daniela Hubl; Thomas Koenig (Brain Topography, 2016)

Short-Term Cuprizone Feeding Verifies N-Acetylaspartate Quantification as a Marker of Neurodegeneration - Barbara Maria Krauspe; Wolfgang Dreher; Cordian Beyer; Werner Baumgartner; Bernd Denecke; Katharina Janssen; Claus-Dieter Langhans; Tim Clarner; Markus Kipp (Journal of Molecular Neuroscience, 2015)

Iron oxide mineralogy and stable iron isotope composition in a Gleysol with petrogleyic properties - Tim Mansfeldt; Stephan Schuth; Werner Häusler; Friedrich E. Wagner; Stephan Kaufhold; Mark Overesch (Journal of Soils and Sediments, 2012)

Wasserkraft als Sanierungsmotor für hydromorphologische Belastungen? - Alois Lashofer; Werner Hawle; Tim Cassidy; Michael Pucher; Josef Fürst; Bernhard Pelikan (WASSERWIRTSCHAFT, 2011)

Cuprizone Treatment Induces Distinct Demyelination, Astrocytosis, and Microglia Cell Invasion or Proliferation in the Mouse Cerebellum - Angela Groebe; Tim Clarner; Werner Baumgartner; Jon Dang; Cordian Beyer; Markus Kipp (The Cerebellum, 2009)

Circular stationary solutions in two-dimensional neural fields - Herrad Werner; Tim Richter (Biological Cybernetics, 2001)